HARTWIG, H. Protección del diseño en Europa (icade. Journal of the Faculty of Law at Universidad Pontificia Comillas, 2013)
HARTWIG, H., Desinschutz in Europa (Design Protection in Europe). Entscheidungen europäischer und nationaler Gerichte (Decisions of European and National Courts), Vol. 1, Carl Heymanns Verlag GmbH, Köln- Berlin- München, 2007, 259 págs.